Mobility of top incomes in Germany - Katharina Jenderny (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2013)
Mobility of top incomes matters for both the openness of the income elite and the share of total income that this group receives. It is thus an important complement information to the growing snapshot literature on top income concentration. I use microlevel panel data of German income tax files that is highly representative for top income households. Top income mobility is assessed in four dimensions: (i) its stability over time, (ii) the degree of mobility between top income fractiles, (iii) the degree of mobility between equally sized groups and mobility in ranks, both of which do not depend on fractile sizes, and (iv) mobility's impact on distributional results. Mobility in terms of annual fractile changes is high between the richest top income fractiles, which is primarily due to tiny fractile sizes. When the fractiles' sizes are controlled for, top income recipients' mobility is lower than that of lower income tax units.
Keywords: D31; D63; H24; 330; income distribution; inequality; top incomes